Investigating the effects of enhanced catecholamine stimulation in stem cell-derived cardiomyocytes - Samodien, Kauthar (Department of Human Biology, 2026)
Background: Heart failure contributes significantly to global mortality rates and is even projected to surpass infectious diseases as the primary cause of death in Africa by 2030. Autonomic imbalance, marked by an exaggerated cardiac sympathetic tone and parasympathetic withdrawal, is a prominent characteristic of heart failure. As the atrial and ventricular pumping efficiency declines, this sympatho-overexcitation induces a compensatory stress response known as cardiac remodelling which adjusts the structure and function of mainly the myocardium to restore cardiac output. However, chronic sympatho-overexcitation is associated with maladaptive and pathological remodelling, which exacerbates the effects of heart failure and further elevates the stress response. Thus, a vicious cycle of sympathetic overdrive and maladaptive remodelling is established. At the cellular level, the remodelling is mediated through the sustained stimulation of β-adrenergic receptors by catecholamines via mechanisms that are not yet clear but proposed to involve altered signalling of molecules such as stress-response growth factors. One such growth factor is the transforming growth factor beta 1 (TGF-β1) which plays a pivotal role in cardiac development but is also upregulated during heart failure. However, the contribution of TGF-β1 to cardiac remodelling has not been fully explored and may possesses therapeutic significance. As such, the disease remains difficult to treat or prevent since the molecular mechanisms involved, and nature of the cardiac phenotype are not completely understood. Aims and Objectives: The aim of this study was to investigate the mechanisms underlying catecholamine-induced cardiac remodelling at the cellular level. The specific objectives were to: (1) establish and validate a model of sympathetic overdrive in stem-cell derived cardiomyocytes, (2) characterise the structural and functional cardiac phenotype (3) evaluate the role of the TGF-β1 in cardiac remodelling. Methods: Pluripotent mouse embryonic stem cells were differentiated, in vitro, into pulsatile cardiomyocyte-like cells via the formation of cell clusters called embryoid bodies (EBs). A model of sympathetic overdrive was induced by treating the EBs with a synthetic catecholamine, isoprenaline (10μM isoprenaline for 72 hours) as was determined by the results of a preliminary dose-response test. The EB growth patterns were monitored using light microscopy and the images were analysed with ImageJ software. Beating characteristics were captured by time-lapse light microscopy imaging and analysed with a motion detector software called Myocyter. Molecular analyses were performed using western blot, immunocytochemistry, and the 5ethynyl-2'-deoxyuridine (EdU) stain cell-proliferation assay. Results: Isoprenaline stimulation induced a four-fold increase in the EB beating rate compared to the untreated or EBs treated with the β-adrenergic receptor antagonist, pindolol (0.2μM), indicating an altered chronotropic response of the EBs to isoprenaline. However, isoprenaline significantly decreased the amplitudes of contraction. In addition, the application of the ryanodine receptor agonist, caffeine (0.5mM, 5 minutes), resulted in a ten-fold increase in the amplitude of contraction for iso-treated EBs compared to a two-fold increase in the untreated and pindolol-treated EBs. Structurally, isoprenaline resulted in the formation of denser and more spherical EBs, however, EB sizes were not significantly different among the treatment groups. Furthermore, isoprenaline produced a two-fold increase in the number of EdU-positive nuclei, which is indicative of increased cellular proliferation. Isoprenaline resulted in an increased nuclear localization of the phosphorylated component of the TGF-β1 downstream intracellular mediator SMAD3 (p-SMAD3), compared to the peri-nuclear localisation of p-SMAD3 observed in the untreated and pindolol-treated cells. Furthermore, TGF-β1 inhibition with LY2109761 (25μM) in isoprenaline-treated EBs restored the peri-nuclear localisation of p-SMAD3. In addition, the inhibition of TGFβ1 attenuated the effects of isoprenaline on EB density, sphericity and contractile function thus validating the role of the TGF-β1- SMAD3 signalling pathway in isoinduced cardiac changes. Conclusion: Enhanced isoprenaline stimulation results in β-adrenergic receptor mediated changes in cardiac morphology, proliferation, and function, and is associated with increased TGF-β1-SMAD3 signalling and thus necessitates investigation into the downstream effectors of this pathway.